Effects of tDCS on Depression and Comorbid Generalized Anxiety Disorder: A Brain Function Imaging Case Report - Wu, Yuwei; Tang, Lin; Shi, Xiaolong; Zhou, Zhiqing; Li, Yuanli; Shan, Chunlei (Frontiers in Neurology, 2022)
Background: Transcranial direct current stimulation (tDCS) is a type of noninvasive brain stimulation technique that has proven effective for neuropsychiatric disorders. Generalized anxiety disorder (GAD) and depression are common psychiatric disorders that often are comorbid, meaning they occur simultaneously. Current evidence supports the value of tDCS for GAD. This case study explores the effect of tDCS on clinical symptoms and cerebral function in a patient with comorbid GAD and depression. Methods: Our subject was a semiprofessional athlete diagnosed with comorbid GAD and depression. Symptoms included palpitations, sweating, continuous tension, and anxiety. We designed an A-B-A experimental protocol and used the Beck Anxiety Index (BAI), Beck Depression Index (BDI), and Pittsburgh Sleep Quality Index (PSQI) as assessment tools. Treatment consisted of 2 sessions of 15 days each, separated by a 3-week washout period. We collected functional near-infrared spectroscopy (fNIRS) data before and after both sessions, as well as fNIRS data immediately after the first treatment in both sessions. In addition, we collected functional magnetic resonance imaging data before and after the second session. Results: After the first session, the scores of the three questionnaires (BAI, BDI and PSQI) decreased significantly, which showed the trend of improvement. The functional connection of bilateral prefrontal partial channels decreased significantly immediately after tDCS treatment. The results of the fNIRS before the second-session treatment showed that prefrontal connectivity returned to the state before the first intervention after the washout period. The results of the fNIRS after the second session treatment showed that the symptoms of depression and anxiety alleviated. The results of the fNIRS showed that the prefrontal connectivity decreased again. Conclusion: In the treatment of comorbid GAD and depression, tDCS can alleviate symptoms and improve sleep quality and social behavior. The study also showed that fNIRS can be a safe, simple, and efficient method to assess brain activity.